Epidemiology of Hypertension Counseling, Healthy Lifestyle (PHBS), Integrated Health Post (Posyandu), Immunization, and Complimentary Health Assessments in Sampalan Lega Village, Cintaraja, Tasikmalaya - Wuri Ratna Hidayani; Rini Febriani; Hapi Apriasih; Aditya Nugraha (Research and Social Study Institute, 2026)
Background: The factors motivating this community service initiative include the public's insufficient comprehension of epidemiology, risk factors, the significance of PHBS in hypertension prevention, the low awareness of immunization's role in addressing stunting, and their restricted knowledge of integrated posyandu. 43 individuals are afflicted with hypertension due to an unhealthy lifestyle, comprising twenty individuals with a high sodium intake and fifteen individuals with inadequate physical activity. Moreover, there exists a deficiency in awareness regarding the epidemiology of hypertension and a limited comprehension of clean and healthy living practices, impacting 35 individuals.Aims: This effort aims to enhance public comprehension regarding the significance of health checkups, the role of immunization in preventing stunting in toddlers, the relevance of hypertension in relation to PHBS, and the necessity of an integrated Posyandu.Methods: This community service program encompasses complimentary health assessments, educational initiatives on epidemiology and hypertension prevention through a clean and healthy lifestyle (PHBS), instruction on the significance of immunization in stunting prevention, and education regarding integrated Posyandu services. The intended audience for this exercise comprises 43 individuals from Kampung Sampalan Lega. The tools employed to evaluate the enhancement of community knowledge were observation sheets and interviews.Results: This activity can enhance community knowledge, as demonstrated by the observations and interview findings conducted before and after the counseling, indicating an increase in respondents' understanding. Forty-five individuals, representing 100%, achieved a score of 100 on the observation sheet. The community is expected to consistently visit the health post to monitor their health status. It is anticipated that healthcare staff would persist in enhancing healthcare services at integrated posyandu.